Ethics in adult education: Research into the attitudes of adult learners on the use of artificial intelligence in educational systems - Štetić, Dinko (Oeconomica Jadertina, 2026)
In this paper, the attitudes of adult learners toward the ethical aspects of using artificial intelligence (AI) in educational systems are explored. The development and integration of AI technologies in education raise numerous questions related to privacy, bias, transparency, and accountability, which are key ethical issues in modern education. By using a combination of quantitative and qualitative research methods, data were collected from adult learners enrolled in various educational programs to investigate their perceptions and concerns regarding the use of AI in educational systems. The results show that learners have diverse attitudes towards the application of AI, recognizing the potential benefits in personalization and improving the quality of education, while also expressing concerns about possible negative implications for privacy and ethical standards. This paper contributes to a better understanding of the complexity of ethical issues in adult education, particularly in the context of the increasingly prevalent role of artificial intelligence.
Keywords: ethics, adult education, AI, educational processes